Aplikasi Web Pemetaan Wilayah Kelayakan Tanam Jagung Berdasarkan Hasil Panen di Kabupaten Lampung Selatan - Agung Tri Prastowo; Dedi Darwis; Nurhuda Budi Pamungkas (Universitas Lampung, 2020)
South Lampung Regency is a district with the capital city of Kalianda which dominates agricultural areas, one of which is corn. With the corn harvest spread in each district in the South Lampung Regency, it will attract investors to invest or invest in corn farming in the South Lampung region. This application was built with the aim of making it easier for the community and potential investors to see the potential of the sub-district corn planting area based on the yield in the form of map visualization to make it easier to find the location of the area to be planted with corn. The result of this application is a web-based system in the form of map visualization to show potential areas for planting corn. Based on the results of tests conducted, this application has a percentage score of 85.96% meaning this application is very good to be implemented.